Comunicación intercultural y recursos multimodales del Ministerio de Cultura en la prevención del covid-19 para los awajún a través de Facebook, de marzo a agosto de 2020 - Sánchez, Diana (2025)
This article analyzes the challenges in intercultural communication between the Ministry of Culture (Mincul) and the Awajún indigenous people during the covid-19 pandemic, highlighting the importance of multimodal resources for effective information shared. Through a qualitative analysis of the informational materials disseminated by Ministry of Culture on Facebook from March to August 2020, as well as the role of translators, interpreters, and activists, linguistic and cultural barriers that limited the effectiveness of communication were identified. The research reveals the urgent need for resources to be culturally relevant and respectful of indigenous languages, such as Awajún, to ensure better understanding and access to information. It concludes that effective intercultural communication is crucial, especially in times of crisis, to ensure the inclusion and empowerment of indigenous communities.